Analisis Karakteristik Masyarakat Agroforestri Tanaman Sengon di Hutan Produksi Wilayah KPH Cantung - S Saufi; Muhammad Saleh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This research was conducted to find out: (1) analyzing the characteristics of agroforestry communities or agroforestry farmers in the Cantung area by stating, age, education, occupation, and number of family members. (2) find out what agroforestry patterns the people of Cantung are doing with sengon and other agricultural crops. (3) knowing the role of agroforestry in the income of the Cantung community which is under the Forest Management Unit (FMU). This study used respondents as many as 25 agroforestry farmers in the KPH Cantung area. Processing of analysis in this study was carried out in grouping tabulation of numbers using the calculation formula and entered into Excel. The results obtained in the study showed that intercropping is the best cropping pattern currently carried out by agroforestry farmers in the Cantung area because the average land owned by farmers is not so extensive, agroforestry plantation yields play a large role on farmers' incomes and varying community characteristics.